Transcription factor SlbZIP12 affects tomato shelf life by mediating the ethylene biosynthesis at postharvest stage - Abdul Karim Amin; Wenyi Zhu; Pengwei Li; Shi Shi; Mengru Qin; Yan He; Huizhen Zhang; Hong Yao; Shuqi Chen; Hamza Latif; Mohammad Yousof Soltani; Mahmood Hemat; et al. (Postharvest Biology and Technology, 2026)

Ultrasound-assisted cleaning and drying in food processing: Mechanisms, applications, and quality enhancements - Chunhua Dai; Yun Pan; Man Zhou; Lihui Zhang; Liurong Huang; Yuqing Duan; Ronghai He (Food Control, 2026)

Biocontrol potential of Bacillus velezensis lut-Y1: Antifungal lipopeptides against postharvest fungi Alternaria alternata and Penicillium expansum - Hui-Jun Yuan; Yan-Sen Li; Wen-Jin Ma; Tian-Kun Zhao; Zhen-Dong Wang; Miao-Miao He; Shi-Man Yu; Yan-Ying Xu (Physiological and Molecular Plant Pathology, 2026)

Mechanistic analysis of enhanced methane production during anaerobic digestion of coal by different exogenous microbial consortia - Hongyu Guo; Haodong He; Shufeng Zhao; Xiao Zhou; Man Wang; Zhaoying Chen; Daping Xia (Journal of Environmental Chemical Engineering, 2026)

Rationally designed aluminum-supported g-C3N4: An efficient and halogen-free catalyst for CO2-epoxide cycloaddition - Man Zhao; Wen-Jun Xie; Shan-Shan Chen; Hong-Ru Li; Liang-Nian He (Journal of Environmental Chemical Engineering, 2026)

Formulation-resolved VOC emission factors measured in a dynamic chamber and corresponding secondary formation potentials for selected architectural paints - Fanglin Wang; Ka Hei Lui; Donger Lai; Guoyang Lei; Chung Ling Man; Yansu He; Dasa Gu; Zhe Wang; Man Nin Chan; Donald R. Blake; Kin Fai Ho (Environmental Pollution, 2026)

Structurally decoupled strongly hydrophobic biocathode enables high-performance flexible enzymatic biofuel cells for self-powered sensing - Jie Gao; Ang Xu; Jia Wu; Jinlong He; Ping Wang; Ying Liu; Qiang Wang; Bo Xu; Yuanyuan Yu; Man Zhou (Chemical Engineering Journal, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Robust identification of known and unknown weeds with crop center localization based on Open-set object detection - Lamin L. Janneh; Leilei He; Bryan Gilbert Murengam; Xiaojuan Liu; Mbemba Hydara; Man Xia; Rui Li; Yanxin Zhang; Longsheng Fu (Precision Agriculture, 2026)

Wastewater treatment process optimization in stochastic game based on multiagent deep reinforcement learning - Guanghua Wang; Xingyu Wang; Fan Luo; Yi Man; Zhenglei He; Sai Liang; Zhifeng Yang (Water Research, 2026)

Phospholipid profiles of human milk fat globule membrane across lactation stages: A comprehensive analysis from colostrum to mature milk - Ziyi Zhang; Xuemin Wang; Sufang Duan; Ignatius Man-Yau Szeto; Zhong Wang; Xiuxiu Zhang; Jian He; Xiaodong Li; Zhe Zhao; Shuxuan Li (International Dairy Journal, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

DAF-16/FOXO insulin signaling modulates F-53B toxicity by regulating intestinal redox homeostasis and permeability in Caenorhabditis elegans - Qinlin Wu; He Chen; Man Qu (Chemico-Biological Interactions, 2026)

In-situ growth of covalent organic frameworks on 3D‐printed monolithic microfluidic chips for online analysis of naphthalene and its metabolites in cells - Qiulin Zhang; Beibei Chen; Zhen Zhou; Yong Liang; Yuning Hu; Man He (Analytica Chimica Acta, 2026)

Design, synthesis, and biological evaluation of novel trifluoromethyl-substituted quinolinone derivatives targeting triple-negative breast cancer - Mei Zhang; Man Chen; Yimin Yang; Sirui Qiao; Qiuli Yao; Jia Jia; Xueyu Man; Chun-Yang He (Molecular Diversity, 2026)

Myricetin activates innate antiviral immunity during PRRSV infection in MARC-145 cells - Aiyang Wang; Weizhen Chen; Bo Wang; Man Tong; Xing Feng; Shaojun He; Hongjie Fan; Liujun Zhang (Veterinary Immunology and Immunopathology, 2026)

Small-strain dynamic response of recycled concrete aggregate: A mechanistic study of the coupled influence of cement mortar coating and compaction state - Man LI; Matthew Richard COOP; Guojun CAI; Huan HE; Ruifeng Chen; Zhexun Liu (Transportation Geotechnics, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Association between residential greenness exposure and excessive gestational weight gain: A dual-center birth cohort study - Xuejin Li; Yanshen Zhang; Yijun Liu; Xiuping Dou; Man He; Yao Huang; Yang Su; Bingying Zhang; Weidong Luo; Qingmei Lin; Yongjun Shi; Boyi Yang; et al. (Environmental Research, 2026)

Structural characterization of an acetylated glucomannan from Aloe barbadensis and its alleviation of murine colitis via coordinated ECM repair and microbiota-metabolism actions - Xiaofeng Guo; Jianmin Guo; Man Li; Jinzi Chen; Lu Li; Xueli Tong; Haiyang Yin; Weijie Xu; Mengmeng Wang; Xie He; Zhihang Zhong; Wei Yang; et al. (Carbohydrate Polymers, 2026)

A meter-level resolution least-cost-path method for fast urban ventilation assessment: Preliminary validation using CFD and wind tunnel - Yueyang He; Kai Gao; Xinrui Guo; Man Kit Leung; Dicken Poon; Yuxiu Zu; Tim Huang; Kenneth Leung; Jenny Zhao; Kam Sing Wong; Chak Sang Yue; Yuk-ching Cheung; et al. (Building and Environment, 2026)

Shrub-mediated shifts in herbaceous foliar elemental composition and coupling along an aridity gradient across the Inner Mongolian steppe - Peng He; Jiang Chen; Josep Peñuelas; Jordi Sardans; Lina Xie; Heyong Liu; Liang Man; Chengcang Ma; Xingguo Han; Yong Jiang; Mai-He Li (Plant and Soil, 2026)

Area and Growth Contributions to Dynamics of Forest Biomass Carbon Stocks in Northeast China - Chunhua Zhang; Yue Cao; Ran Wang; Wei He; Haoran Man; Jie Ma; Dan Lu; Shoujian Zhang (Chinese Geographical Science, 2026)

Sensitive detection of methylated DNA by elemental labeling inductively coupled plasma mass spectrometry using exponential amplification and DNAzyme - Shaocheng Liu; Beibei Chen; Man He; Bin Hu (Analytica Chimica Acta, 2026)

Seafloor methane seepage under anoxic conditions in the Early Jurassic Laurasian Seaway - Yiheng Wu; Tianchen He; Marisa S. Storm; Dinggui Wu; Jinchao Liu; Muhammad Tahir Abubakar; Man Li; Yuchen Zheng; Ruikang Su; Hepin Wu (Frontiers in Marine Science, 2026)
The Early Jurassic was punctuated by repeated intervals of enhanced organic matter preservation. Subsequent methane release from organic-rich strata via methanogenesis is locally recorded by seep structures. The geochemical characteristics of these seep structures remain poorly constrained. This study presents a comprehensive inorganic geochemical analysis of carbonate-cemented seep mounds from Sinemurian and Toarcian cold seep systems at Kilve (Somerset, U.K.) and Ravenscar (Yorkshire, U.K.), situated along the Laurasian Seaway. Iron speciation, redox-sensitive trace metals, and carbon and sulfur isotope analyses indicate that methane seepage at these mounds occurred under primarily anoxic ferruginous depositional conditions. Pyrite δ 34 S values suggest microbial sulfate reduction in active sulfate-methane transition zones (SMTZ), reflecting sulfate-driven anaerobic oxidation of methane (SD-AOM), partly under sulfate-limited conditions. The results suggest that methane flux from underlying organic-rich strata was partially mitigated by microbial processes within the sediment before reaching the water column. Variations in sulfate supply and methane may have influenced the efficiency of this methane filter and led to changes in the methane flux across the sediment-water interface.

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

Ferrocene-MOF derived nanoporous carbon for magnetic solid-phase extraction of p‑phenylenediamine antioxidants and quinone-derivatives in various environmental water samples - Jia-Qi Zhao; Bing-Dan Wang; Ao-Ran Wang; Yu-Tian Cai; Shou-Fang Jiang; Hai-Jie Li; Yu He; Man-Man Wang (Journal of Hazardous Materials, 2026)

3D printing integrated trapezoidal spiral chip coupled with ICP-MS for single-cells analysis - Yunyao Yin; Beibei Chen; Man He; Bin Hu (Analytica Chimica Acta, 2026)

Differences in DHA stability of DHA-enriched yogurts during low-temperature storage - Senyang Hu; Jianmin Zou; Hejing Tang; Wenhua Jin; Jian He; Zihao Wang; Yang Yang; Chang Liu; Pengjie Wang; Wei Tan; Ignatius Man-Yau Szeto; Xiaoyu Wang; et al. (Food Research International, 2026)

Unraveling hydration and physicochemical property modulation in potato starch gels through multiscale structural orientation induced by uniaxial stretching–drying - Liu Xiong; Yuting He; Xianzhi Liu; Man Li; Zhongxiu Wang; Shengtian Zhang; Qingjie Sun (Food Hydrocolloids, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

A multi-scale investigation of the effect of cement mortar coating on the small-strain shear stiffness of recycled concrete aggregate - Man Li; Matthew Richard Coop; Guojun Cai; Huan He; Yi Cai; Chen Zhang (Journal of Cleaner Production, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Construction of recombinant Lactococcus lactis expressing VP1 from duck hepatitis a virus types 1 and 3 and evaluation of its immune effect - Yafei Qin; Yaru Fan; Meijuan Zhang; Saisai Zhao; Xinhong Man; Dalin He; Youxiang Diao; Junxun Li; Jingdong Hu; Yi Tang (Veterinary Research Communications, 2026)

Various human activities during the Great Acceleration across China reflected by lake sediments - Guonai Li; Zhangdong Jin; Jianqi Man; Mao-Yong He; Yuanyuan Cheng; Rujun Guo; Li Deng (Applied Geochemistry, 2026)

Multi-View Point Cloud Registration Method for Automated Disassembly of Container Twist Locks - Chao Mi; Teng Wang; Xintai Man; Mengjie He; Zhiwei Zhang; Yang Shen (Journal of Marine Science and Engineering, 2026)
With the continuous expansion of maritime trade scale, ports have put forward increasingly higher requirements for transshipment efficiency. Container twist lock disassembly is a key link in the loading and unloading process, and its automation level has a significant impact on the ship’s berthing time at the port. Aiming at the demand of automated disassembly for high-precision 3D vision, this paper proposes a multi-view point cloud local registration method for twist lock recognition. First, Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN) is used to extract the keyhole region with the highest overlap in multi-view point clouds, reducing the interference from non-overlapping structures. Then, a two-stage strategy of “coarse registration + fine registration” is adopted: initial alignment is achieved through Random Sample Consensus (RANSAC), and the Iterative Closest Point (ICP) algorithm is improved by combining adaptive distance threshold and normal consistency constraint to complete fine registration. Experimental results show that the proposed method outperforms the global registration scheme in both accuracy and efficiency: the Root Mean Square Error (RMSE) is reduced to 2.15 mm, the Relative Mean Distance (RMD) is reduced to 1.81 mm, and the registration time is approximately 2.41 s. Compared with global registration, the efficiency is improved by 44.2%, which can meet the real-time requirements of continuous operation at automated terminals for the perception link and the time constraints for subsequent manipulator control. The research results preliminarily verify the application potential of this method in the scenario of automated twist lock disassembly.

Responses of Greenhouse Gas emissions, Crop yields, and Soil Properties to Biochar Application of Three Major Cereal Food Crops: A Global Meta-Analysis of Field Studies - Hao He; Man Li; Mingjie Chen; Lin Zhao; Qi Li; Zhenghua Hu; Shuyun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Photoelectrotrophy: a novel mode of microbial metabolism and its biogeochemical effects - Youming Diao; Zihan Xie; Xueying He; Yong Jiang; Shaofu Huang; Man Chen (Reviews in Environmental Science and Bio/Technology, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

The function of OsRAD51A1 gene in meiotic stability and high seed-setting rate of tetraploid rice - Pincang Lv; Meng Fang; Yuandong Xing; Man Wang; Rongjie Qiu; Chang Yao; Hao Wu; Xiaolong Peng; Xianhua Zhang; Yuchi He; Detian Cai; Zhaojian Song (Plant Cell Reports, 2026)

Geniposide Inhibits Non-Small Cell Lung Cancer by Regulating Proliferation, Apoptosis, Invasion, Migration, Epithelial-Mesenchymal Transition, and Cancer Stem-Like Cell Property Via Wnt/β-Catenin Pathway - Haifa He; Yin Li; Yuan Wang; Man Li (Biochemical Genetics, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

A comparative study of CO2 emissions from provincial transportation industry before and after COVID-19 in China - Yi-jing He; Wen Wen; Xing-man Zhang; Yang Su; Xing Gao (Environment, Development and Sustainability, 2026)

Triazine-based nitrogen-rich porous polymeric material for selective and efficient dynamic capture of low-concentration iodine vapor and methyl iodide - Man He; Hui Zhu; Guoren Li; Tao Duan; Jiehong Lei (Journal of Hazardous Materials, 2026)

Multiple enhanced PMF framework addressing ambient processing and factor allocation for VOC source apportionment - Zhining Zhang; Xinyue Zhao; Chun Deng; Hanyang Man; Lijuan Qi; Junchao Zhao; Zhenyu Luo; Hongli Wang; Shengao Jing; Tao He; Kebin He; Huan Liu (Journal of Cleaner Production, 2026)

Selenium nanoparticles stabilized by polyphenols from black bean husk: synthesis, characterization, stability and application in functional foxtail millet sprouts - Meng Li; Yunfeng Xu; Guowei Man; Xiangxiang He; Lei Luo; Jinle Xiang (Food Chemistry, 2026)

Improving the presentation of HONO in CMAQ based on observations over the Yangtze River Delta Region - Shuxian Zhang; Jie Yao; Honghui Xu; Jun He; Man Yue; Meng Shan; Fan Meng; Xiaoai Jin; Ziqi Jin; Huansang Chen; Yilei Dong (Atmospheric Research, 2026)

ARC-18 Alleviates Alzheimer-like Pathology and Cognitive Deficits via AdipoR1-Mediated Activation of Autophagy and Modulation of APP Processing - Shangming Li; Bocheng Xiong; Nan Xu; Lulin Nie; Kaiwu He; Guiliang Zhang; Chongyang Chen; Zaijun Zhang; Maggie Pui Man Hoi; Xifei Yang (Molecular Neurobiology, 2026)

Dynamic Characterization of the 2009 Jiweishan Rockslidein Wulong, China, Based on Broadband Seismic Observations - Kai Chen; Meng Zhang; Man-qiu He; Jiang Yi; Tong-jun Wang (Applied Geophysics, 2025)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Smart textiles: Sustainable, self-powered, portable, and durable wearable textiles for human health monitoring - Man Zhou; Jia Wu; Liang Huang; Miao Miao; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2025)

Methods and experiments for analysing hard-bottom layer changes and monitoring wheel sink depth in paddy fields - Tuanpeng Tu; Xiwen Luo; Lian Hu; Sun-Ok Chung; Jie He; Runmao Zhao; Pei Wang; Gaolong Chen; Dawen Feng; Mengdong Yue; Zhongxian Man; Md Rejaul Karim; et al. (Computers and Electronics in Agriculture, 2025)

Discovery of milk-derived antimicrobial peptides in human milk by DeepMAMP based on peptidomics technology and deep learning method - Wenhao Yu; Xinchen Zhang; Yang Yu; Dengcai Zhao; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Li Liu; Yan Jin (Food Chemistry, 2025)

A unified framework for morphological and intra-particle pores reconstruction in calcareous sand using spherical harmonics and random field methods - Yong He; Huan He; Yuanhang Li; Guojun Cai; Man Li (Computers and Geotechnics, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

Polyphenolic nanodots loaded multi-layer MXene for strong, tough and rapidly biodegradable polyvinyl alcohol/starch nanocomposites with self-healing ability and improved aging resistance - Sha Yao; Jiaojiao Jiang; Qiaoyu He; Man Chen; Jingjing Luo; Bangchao Zhong; Zhixin Jia (Carbohydrate Polymers, 2025)

Synergistic effects of biochar-microbial inoculants on greenhouse gas mitigation in paddy ecosystems: organic substitution and enzyme driven emission reduction - Kun Zhou; Keqi Zhao; Xiaobing Zhang; Jiachao Zhang; Man Yu; Liuqin He; Lin Luo; Fangying Yu; Lihua Zhang; Xichen Zhao (Biocatalysis and Agricultural Biotechnology, 2025)

Ammonium removal characteristics and metabolic mechanisms of the sulfate-tolerant strain Halomonas piezotolerans X0511 - Xiao You; Dongjian He; Man Jiang; Mengting Zhen; Xia Zhu; Hansheng Wei; Xiaopeng Wang; Ce Shi; Changkao Mu; Chunlin Wang; Yueyue Zhou (Journal of Environmental Management, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Simulation of the enhancement of mass transfer on removal behavior of CH3I in microchannel reactor - Qing He; Lei Zhang; Man Fu; Guorui Zhu (Journal of Environmental Chemical Engineering, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Study on the lateral constitutive model for aged laminated rubber bearings considering frictional sliding - Zhongying He; Jiaqiang Xu; Junfei Huang; Yifan Song; Haoyang Li; Jianxiang Man; Tianxing Liu; Dekang Guo (Engineering Structures, 2025)

Ethanol-regulated synthesis of aluminum−tannic acid network nanofiltration membranes with improved performance for antibiotic removal - Ying Zhang; Luying He; Man Xu; Cunwen Wang; Yanbo Li (Desalination, 2025)

Two-photon phototherapy-mediated activation of natural killer cell immunity for targeted elimination of post-treatment residual hepatocellular carcinoma - Yubo Tan; Yibo An; Yisheng Peng; Man Li; Ziying Wang; Renyuan Liu; Dazhuang Xu; Xinyu Tan; Peiyu Wang; Yaohui He; Bo Li; Gang Liu; et al. (Chemical Engineering Journal, 2025)

A novel strategy of magnetic-dielectric synergistic metamaterials based on multifunctional anisotropic aerogels for superior electromagnetic wave absorption - Chen Li; Yu Gao; Xiao He; Yongkang Lai; Yajie Xie; Weiwei Qi; Qikui Man; Baogen Shen (Chemical Engineering Journal, 2025)

Diurnal NO emission underestimation constrained using overlapping TROPOMI swaths - Qin He; Kai Qin; Xiaolu Li; Lingxiao Lu; Man Sing Wong; Jason Blake Cohen (Atmospheric Environment, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Isolation of two new isomers of fusarin D from Fusarium sp. G10, an endophytic fungus of Iris japonica - Ya-Nan An; An-Le Tan; Xiao-Ying Long; Yue Zhou; Man He; Xiao-Long Tang (Natural Product Research, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

A novel [MMIM]-based ionic liquid extractive distillation process for achieving liquid-phase propylene at 1.8 MPa with enhanced energy-economic-environmental benefits - Chao Guo; Kai Luo; Wei Hou; Xinyu He; Yi Man (Journal of Cleaner Production, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Climate change aggravates the Spatiotemporal imbalance of water resources in the Rice-Wheat rotation region of the middle and lower Yangtze river - Hao He; Man Li; Lin Zhao; Jinge Yu; Qi Li; Zhenghua Hu; Xuesong Zhang (Theoretical and Applied Climatology, 2025)

Dynamic changes of rice sheath non-structural carbohydrates and source-sink balance under elevated atmospheric CO2 concentration and temperature stresses - Hao He; Jiabin Shi; Mingjie Chen; Jing Zhao; Kexi Qu; Man Li; Lin Zhao; Yuanyuan Wang; Zhenghua Hu; Qi Li (Journal of Plant Physiology, 2025)

Estimation of Soil Organic Carbon Stocks Utilizing Machine Learning Algorithms and Multi-source Geospatial Data in Coastal Wetlands of Tianjin and Hebei, China - Rui Yang; Mingyue Liu; Yongbin Zhang; Weidong Man; Jingfen Tong; Dong Liu; Qingwen Zhang; Caiyao Kou; Xiang Li; Yahui Liu; Di Tian; Xuan Yin; et al. (Chinese Geographical Science, 2025)

High-resolution estimation of urban anthropogenic carbon emissions - Zirong Lin; Bo Huang; Jia He; Yizhen Yan; Man Xiao; Qinrui Luo; Zhulin Qi; Xiaotian Ding (Sustainable Cities and Society, 2025)

Modulating the electronic configuration of single-atom nanozymes using cobalt nanoclusters for enhanced mycotoxin degradation - Yaqi Zhang; Huikang Lin; Lan Wang; Lijun He; Yong Man; Bingxuan Jia; Zheng Yan; Shimo Kang; Haijiao Xie; Aibo Wu (Food Chemistry, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Bioactive ion engineered 3D printed TCP scaffolds promote vascularized bone regeneration in diabetic bone defects by restoring mitochondrial homeostasis - Yue He; Man Shu; Zhimin Li; Yun Liu; Ziyang Xu; Kelie Wang; Yu Zhang; Teliang Lu (Chemical Engineering Journal, 2025)

Government-involved urban meteorological networks (UMNs): A global review - Carmen Hau Man Wong; Yu Ting Kwok; Yueyang He; Edward Ng (Urban Climate, 2025)

Dynamics and scenarios of embodied carbon emissions in China’s pulp and paper industry - Xiangyao Liang; Mengna Hong; Yi Man; Zhenglei He (Resources, Conservation and Recycling, 2025)

Iodine crystallization-promoted efficient capture of iodine by nonporous covalent organic polymer - Yong Man; Xiaoshuang Cui; Ruobing Wang; Shiqi Chai; Chenchen Song; Yaming Sun; Renyong Zhao; Lijun He (Journal of Hazardous Materials, 2025)

Optimization of surface modification conditions of jute powder and study of its adsorption behavior and mechanism for Pd(II) - Man Lu; Manman Ge; Yong Li; Guozhen Wang; Xinke Kang; Haiyan Wu; Ling Tan; Haigang Dong; Jianping Xie; Bo He (Journal of Environmental Chemical Engineering, 2025)

Fabrication of electrically conductive polysulfone loose nanofiltration composite membranes with a dually charged separation layer for efficient separation of dye/salt mixtures: Electric-field-assisted formation of porous support layers - Kang Li; Shuhao Qin; Wei Gao; Mingmi Wu; Man Yang; Chengtao Gao; Shengbao He; Huiju Shao (Journal of Environmental Chemical Engineering, 2025)

Global levels and variations of breast milk fatty acids and triacylglycerols: A systematic review and meta-analysis - Xinggang Ni; Zhiyi Zhang; Zeyuan Deng; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Ting Li; Jing Li (Food Chemistry, 2025)

Biomass aerogel: An emerging eco-friendly material for adsorbing pollutants in water - Wei Liu; Chen Dai; Linheng He; Xingyu Liu; Zhiyang Zhao; Wenqian Yan; Man Yuan; Zihao Song; Sheng Cui (Chemical Engineering Journal, 2025)

Nanobody based immunoassay for detection of aquatic virus: Giant salamander iridovirus - Zhihao Xu; Man Liu; Qiyi He; Wenkai Li; Junkang Pan; El-Sayed A. El-Sheikh; Wenzhi Liu; Bruce D. Hammock; Dongyang Li (Analytica Chimica Acta, 2025)

Assessing microplastic and nanoplastic contamination in bird lungs: evidence of ecological risks and bioindicator potential - Mengzhu Wang; Pinxi Zhou; Shane DuBay; Shangmingyu Zhang; Zhixiong Yang; Yibo Wang; Jiayu Zhang; Yiwei Cao; Zhengrui Hu; Xingcheng He; Shirui Wang; Man Li; et al. (Journal of Hazardous Materials, 2025)

Exogenous iron mitigates photo-facilitation of soil organic matter - Yongli Wen; Jiali Wu; Xueting Wen; Zhuoyue Zhang; Jian Wang; Guanghui Yu; Xinhua He; Maohong Xu; Man Cheng; Wenjuan Liu; Jian Xiao (Geochimica et Cosmochimica Acta, 2025)

Dynamic weighing system for dairy cows based on arrayed weighing platforms - Ying Han; Yongsheng Si; Zhijiang He; Qian Li; Zhiruo Li; Man Zhang; Gang Liu (Computers and Electronics in Agriculture, 2025)

Revealing the regulation mechanism of carbon dots on Ni(OH)2 for optimizing methanol electrooxidation activity - Man Zhao; Liwu Qiang; Meng Bai; He Xiao; Li Zhang; Junming Zhang; Tianjun Hu; Baoliang Lv; Shengxiang Wang; Jianfeng Jia (Chemical Engineering Journal, 2025)

Preclinical studies of natural flavonoids in inflammatory bowel disease based on macrophages: a systematic review with meta-analysis and network pharmacology - Shasha Shi; Hao Jiang; Wenke Ma; Zitong Guan; Mengxue Han; Shuai Man; Zhuzhu Wu; Shan He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Homestead withdrawal behaviour of rural migrants in China: The role of joint reform of hukou system and homestead system - Xiao Cui; Eddie Chi Man Hui; Jianfu Shen; Xin Lin; Siyi Wang; Fang He (Journal of Rural Studies, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Integrated transcriptomics and metabolomics reveal changes during Streptococcus thermophilus JM66 fermentation in milk: Fermentation characteristics, flavor profile, and metabolic mechanism - Shasha Cheng; Wenyan Li; Hanying Yang; Baochao Hou; Weilian Hung; Jian He; Chao Liang; Baolei Li; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Research International, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

Ultrathin and flexible carbonized MXene@PAN/Ni films with alternating multilayered structure for superior EMI Shielding, Joule heating and mechanical performance - Man He; Wen Qian; Haoyuan Li; Zhonghui Li; Hao Chen; Yuming Zhou; Xiaohai Bu; Yongjuan Wang (Chemical Engineering Journal, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Designing breezeways to enhance wind environments in high-density cities: A comprehensive analysis of ten morphological parameters - Yueyang He; Carmen Hau Man Wong; Jiyu Deng; Zhixin Liu; Edward Ng (Sustainable Cities and Society, 2024)

Investigating dehumidification and heating performance in a dual evaporator heat pump system for electric vehicles - Kang Li; Mingfei Tan; Yuan Man; Hua Zhang; Binlin Dou; Ni Liu; Tianjiao Zhang; Qize He; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Simulated nitrogen deposition increased herbivore resistance and competitive ability of an invasive plant species over a native co-occurring congeneric species - Tiantian Lin; Zening Wang; Man Ke; Wanci He; Guoqing Zhu; Abdul Manan; Klaas Vrieling; Bo Li (Plant and Soil, 2024)

Hierarchically porous covalent organic framework doped monolithic column for on-line chip-based array microextraction of nonsteroidal anti-inflammatory drugs in microlitre volume of blood - Qiulin Zhang; Beibei Chen; Man He; Bin Hu (Analytica Chimica Acta, 2024)

High water resistance starch based intelligent label for the freshness monitoring of beverages - Yun Wang; David Julian McClements; Zipei Zhang; Ruojie Zhang; Kuang He; Ziqiang Lin; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; et al. (Food Chemistry, 2024)

Utilization of diverse probiotics to create human health promoting fatty acids: A review - Kuang He; Hao Cheng; David Julian McClements; Zhenlin Xu; Man Meng; Yidong Zou; Guanxiong Chen; Long Chen (Food Chemistry, 2024)

The effects of Cl− channel inhibitors and pyrethroid insecticides on calcium-activated chloride channels in neurons of Helicoverpa armigera - Man Chen; Zixuan Ma; Jiayin Hou; Lingna Zhang; Hongmei Li-Byarlay; Bingjun He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

Integrating both restoration and regeneration potentials into real-world forest restoration planning: A case study of Hong Kong - He Zhang; Calvin K.F. Lee; Ying Ki Law; Aland H.Y. Chan; Jinlong Zhang; Stephan W. Gale; Alice Hughes; Martha J. Ledger; Man Sing Wong; Amos P.K. Tai; Billy C.H. Hau; Jin Wu (Journal of Environmental Management, 2024)

A synergistic method using ferrous sulfate and cementitious materials to solidify landfilled municipal sludge - Hefu Pu; Xiao He; Ming Min; Chunwei Liu; Man Yuan; Jianfeng Cao (Journal of Environmental Chemical Engineering, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Adaptive variational decomposition for water-related optical image enhancement - Jingchun Zhou; Shuhan Chen; Dehuan Zhang; Zongxin He; Kin-Man Lam; Ferdous Sohel; Gemine Vivone (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Insight into selenium biofortification and the selenite metabolic mechanism of Monascus ruber M7 - Lisha Zhu; Pengcheng Long; Man Hu; Liling Wang; Yanchun Shao; Shuiyuan Cheng; Xingxing Dong; Yi He (Food Chemistry, 2024)

Metabolism and transcriptional response mechanisms insight into the Lacticaseibacillus paracasei under the intervention of milk powder storage by-products - Yu Shen; Renyi Geng; Jian He; Baochao Hou; Weilian Hung; Xiaoyan Pei; Xu Wang; Chaoxin Man; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

A sustainable approach: Repurposing harmful algal biomass as carbon-based catalysts for nitrogen fertilizer electrosynthesis from nitrate and CO2 - He Wang; Shuaishuai Man; Han Wang; Volker Presser; Qun Yan (Chemical Engineering Journal, 2024)

Trace rare earth elements analysis in atmospheric particulates and cigar smoke by ICP-MS after pretreatment with magnetic polymers - Xin Zhou; Lingyun Gui; Ziyang Lu; Beibei Chen; Zhekuan Wu; Zhen Zhou; Yong Liang; Man He; Bin Hu (Analytica Chimica Acta, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Adaptive roles of cytokinins in enhancing plant resilience and yield against environmental stressors - Nishbah Mughal; Noman Shoaib; Jianhua Chen; Yang li; Yuhong He; Man Fu; Xingyun Li; Yuanyuan He; Jinya Guo; Juncai Deng; Wenyu Yang; Jiang Liu (Chemosphere, 2024)

Multi-constraint improved RS path planning method for unmanned rice direct seeding machine - Lian Hu; Kang Hou; Jie He; Zhongxian Man; Jiasheng Xie; Pei Wang; Tuanpeng Tu; Ruitao Gao; Le Zi; Yufeng Huang; Mingjin Li; Shuaiqi Ding; et al. (Computers and Electronics in Agriculture, 2024)

Magnetite-mediated shifts in denitrifying consortia in bioelectrochemical system: Insights into species selection and metabolic dynamics - Ziang Kong; He Wang; Han Wang; Shuaishuai Man; Qun Yan (Water Research, 2024)

Efficient electrochemical nitrate reduction by iron phthalocyanine nanorods decorated on multi-walled carbon nanotubes - Wei Wang; Minzhang Li; Man Liang; Yongwang Lu; Qinyu He; Fuming Chen (Journal of Cleaner Production, 2024)

Mechanistic insights into the changes of biological activity and physicochemical characteristics in Lacticaseibacillus paracasei fortified milk powder during storage - Yu Shen; Chao Miao; Ming Ma; Zizhu Zhen; Jian He; Xiaoyan Pei; Yu Zhang; Chaoxin Man; Qianyu Zhao; Yujun Jiang (Food Chemistry, 2024)

Population identification and genetic diversity analysis of Fritillaria ussuriensis (Fritillaria) based on chloroplast genes atpF and petB - Xin Wang; Zhifei Zhang; Yue Shi; Jinhui Man; Yuying Huang; Xiaoqin Zhang; Shanhu Liu; Gaojie He; Kelu An; Laha Amu; Wenqin Chen; Ziqi Liu; et al. (Journal of Applied Genetics, 2024)

Integration of engineering microbial consortium and boosting extracellular amylase of B. amyloliquefaciens for intensifying bioconversion of food waste into lipopeptides - Jia-Xuan He; Zheng-Jie Hou; Bin Qiao; Ming-Zhu Ding; Chun-Yang Cao; Yu-Miao Zhang; Qiu-Man Xu; Jing-Sheng Cheng (Journal of Environmental Chemical Engineering, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Analysis of phytochemical components of Tibetan medicine Pedicularis flava and Pedicularis muscicola by GC-MS and UHPLC-TOF-MS - Wentao Yu; Man Luo; Huan Wu; Yayun Yu; Junmao Li; Minzhen He; Yunlin Feng; Shilin Yang; Wugang Zhang; Min Yao (Natural Product Research, 2024)

In situ synthesis of porous metal-organic frameworks NH2-UiO-66 on tea stem biochar and application in odours adsorption - Xiaorong Dai; Leiping Wang; Zun Man; Yuxuan He; Wei Wang; Fangcong Lin; Junjie Zhu; Dezhao Liu; Hang Xiao; Kaiying Wang (Environmental Pollution, 2024)

Biomimetic artificial nacre-like microfiber of Co/C modified cellulose nanofiber/Ti3C2Tx MXene with efficient microwave absorption - Man He; Xuelian Lv; Hao Peng; Yuming Zhou; Haoyuan Li; Zhonghui Li; Yongjuan Wang; Xiaohai Bu (Chemical Engineering Journal, 2024)

Impact of climate change on the potential allocation of resources of rice cultivation in Yangtze-Huai Rivers region: a case study of Anhui Province, China - Hao He; Mingjie Chen; Man Li; Kexi Qu; Huihui Dang; Qi Li; Zhenghua Hu; Qing Zhang (Theoretical and Applied Climatology, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Elevated CO2 results in modified N2O emissions from paddy rice fields - Hao He; Zhurong Wu; Yuanyuan Wang; Chao Liu; Mingjie Chen; Kexi Qu; Man Li; Jing Zhao; Zhenghua Hu; Qi Li (Nutrient Cycling in Agroecosystems, 2024)

Comparison of change-based and shape-based data fusion methods in fine-resolution land surface phenology monitoring with Landsat and Sentinel-2 data - Caiqun Wang; Tao He; Dan-Xia Song; Lei Zhang; Peng Zhu; Yuanbin Man (Science of The Total Environment, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

Insights into synergetic modulation of nickel sites over graphene by introducing tungsten and light for efficient methanol electrooxidation - He Xiao; Wenxiang Wang; Man Zhao; Zimei Fu; Meng Bai; Li Zhang; Junming Zhang; Ergui Luo; Jian Zhang; Haishun Wu; Jianfeng Jia (Chemical Engineering Journal, 2024)

Advances in understanding the regulation effect of carbon dots on intrinsic activity of metal and metal-free catalysts for electrocatalysis reaction - Meng Bai; Zimei Fu; Chunmei Liu; Peipei Zhao; Jiamin Ma; Wenxiang Wang; He Xiao; Junwei Wu; Man Zhao; Jianfeng Jia (Chemical Engineering Journal, 2024)

VOC and IVOC emission features and inventory of motorcycles in China - Zhining Zhang; Hanyang Man; Junchao Zhao; Wendong Huang; Cheng Huang; Shengao Jing; Zhenyu Luo; Xinyue Zhao; Dawei Chen; Kebin He; Huan Liu (Journal of Hazardous Materials, 2024)

Simple and rapid ionic liquid-based one-, two-, three-phase transition microextraction for efficient extraction of trace organic pollutants and elimination of lipid co-extractives from fatty food matrices - Yong Man; Zhen Yang; Yaming Sun; Wenjie Zhao; Guoqiang Xiang; Lijun He (Food Chemistry, 2024)

Effect of phytic acid on the structure, properties and oil absorption of wheat flour - Yuanhui Chen; David Julian McClements; Kuang He; Xinwen Peng; Zhenlin Xu; Man Meng; Hangyan Ji; Jianwei Zhao; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2024)

Breathable and washable MXene@gallic acid cross-linked textile assisted by borax for personal multi-protection wearables - Biaobiao Yan; Xiaoting Liao; Tianlei Sun; Leilei Wu; Zhenfei Guo; Man Zhou; Yuanyuan Yu; Qiang Wang; Chaobin He; Ping Wang (Chemical Engineering Journal, 2024)

Histidine tag modified magnetic beads for analysis of arsenic binding proteins - Kai Nan; Man He; Beibei Chen; Bin Hu (Analytica Chimica Acta, 2024)

Experimental and modeling study of adsorption behavior of CH3I over microchannel reactors - Qing He; Lei Zhang; Peize Han; Man Fu; Guorui Zhu (Process Safety and Environmental Protection, 2024)

WPS:A whole phenology-based spectral feature selection method for mapping winter crop from time-series images - Man Liu; Wei He; Hongyan Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A versatile AIE probe with two cross-talk-free emissions for dual detection of SO2 and viscosity and its application in food and biological imaging - Di Zhang; Min Wang; Man Li; Lin Liu; Ran Duan; Nana Xue; He Chen; Lijun Shang; Tieliang Wang; Xujin Wu; Junfeng Zhang (Food Chemistry, 2024)

Enhanced piezoelectric performance of PVDF nanofibers by biomimicking the Spider’s long liquid transport - Man-Yu Qian; Chun-Hui He; Ji-Huan He (Chemical Engineering Journal, 2024)

Longitudinal seismic displacement analysis of Quasi Seismic Isolation Bridge based on Energy-based Multimodal Pushover Method with and without collision - Zhongying He; Jianxiang Man; Yifan Song; Wen Xu; Yutao Pang (Soil Dynamics and Earthquake Engineering, 2024)

Construction of robust silica-hybridized cellulose aerogels integrating passive radiative cooling and thermal insulation for year-round building energy saving - Yanmei Liu; Xiaohai Bu; Runqi Liu; Mingxin Feng; Zewu Zhang; Man He; Jun Huang; Yuming Zhou (Chemical Engineering Journal, 2024)

FeNi alloys encapsulated with N-doped porous carbon nanotubes as highly efficient and durable CO2 reduction electrocatalyst - Li Zhang; Bo Geng; Yang Gao; Hefei Kang; Pengfei Wang; Chunmei Liu; He Xiao; Man Zhao; Jianfeng Jia; Haishun Wu (Chemical Engineering Journal, 2024)

Integration of genetic engineering and multi-factor fermentation optimization for co-production of carotenoid and DHA in Schizochytrium sp - Zi-Xu Zhang; Lu-Wei Xu; Ying-Shuang Xu; Jin Li; Wang Ma; Xiao-Man Sun; He Huang (Bioresource Technology, 2024)

Precursor-oriented design of nano-alumina for efficient removal of antibiotics - Hong Guo; Xia-Yin Yin; Li-Fen Zhang; Zheng-Wu Wang; Man-Man Wang; He-Fang Wang (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Covalent organic frameworks based hierarchical porous hybrid monolithic capillary: Synthesis, characterization, and applications in trace metals analysis - Xiaoxiao Ou; Man He; Beibei Chen; Bin Hu (Journal of Hazardous Materials, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Sustainable regeneration of waste polystyrene foam as cooling coating: Building cooling energy saving, CO2 emission reduction and cost-benefit prospective - Shuangjiang Feng; Lei Yao; Mingxin Feng; Haoran Cai; Xu He; Man He; Xiaohai Bu; Yuming Zhou; Tao Zhang (Journal of Cleaner Production, 2024)

Synergy between copper and cobalt on 3D Co/CuO complex promotes peroxymonosulfate activation - Bo He; Siyuan Jiang; Ce Wang; Zhihao Man; Yilong Hou; Jiangwei Shang; Xiuwen Cheng (Chemical Engineering Journal, 2024)

Nutritional changes in trees during drought‐induced mortality: A comprehensive meta‐analysis and a field study - Peng He; Jordi Sardans; Xiaoyu Wang; Chengcang Ma; Liang Man; Josep Peñuelas; Xingguo Han; Yong Jiang; Mai‐He Li (Global Change Biology, 2024)
Both macronutrients and micronutrients are essential for tree growth and development through participating in various ecophysiological processes. However, the impact of the nutritional status of trees on their ability to withstand drought‐induced mortality remains inconclusive. We thus conducted a comprehensive meta‐analysis, compiling data on 11 essential nutrients from 44 publications (493 independent observations). Additionally, a field study was conducted on Pinus sylvestris L. trees with varying drought‐induced vitality loss in the “Visp” forest in southern Switzerland. No consistent decline in tree nutritional status was observed during tree mortality. The meta‐analysis revealed significantly lower leaf potassium (K), iron (Fe), and copper (Cu) concentrations with tree mortality. However, the field study showed no causal relationships between nutritional levels and the vitality status of trees. This discrepancy is mainly attributed to the intrinsic differences in the two types of experimental designs and the ontogenetic stages of target trees. Nutrient reductions preceding tree mortality were predominantly observed in non‐field conditions, where the study was conducted on seedlings and saplings with underdeveloped root systems. It limits the nutrient uptake capacity of these young trees during drought. Furthermore, tree nutritional responses are also influenced by many variables. Specifically, (a) leaf nutrients are more susceptible to drought stress than other organs; (b) reduced tree nutrient concentrations are more prevalent in evergreen species during drought‐induced mortality; (c) of all biomes, Mediterranean forests are most vulnerable to drought‐induced nutrient deficiencies; (d) soil types affect the direction and extent of tree nutritional responses. We identified factors that influence the relationship between tree nutritional status and drought survival, and proposed potential early‐warning indicators of impending tree mortality, for example, decreased K concentrations with declining vitality. These findings contribute to our understanding of tree responses to drought and provide practical implications for forest management strategies in the context of global change.

Effect of 3D titanium substrates with TiO2 nanotube arrays on photoelectrocatalysis degradation of phenol - He Li; Man Li; Bin Jiang; Ru Liu; Qi Li; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2023)

Runoff and sediment characteristics of a typical watershed after continuous soil erosion control in the red soil region of Southern China - He Wang; Wenxiang Chen; Man Zhou; Zuopin Zhuo; Yue Zhang; Fangshi Jiang; Yanhe Huang; Jinshi Lin (CATENA, 2023)

Towards low-carbon papermaking wastewater treatment process based on Kriging surrogate predictive model - Zhenglei He; Mengna Hong; Hongze Zheng; Jinfeng Wang; Qingang Xiong; Yi Man (Journal of Cleaner Production, 2023)

Superamphiphobic interface-enhanced inorganic coating for multi-environments tolerant and zero-energy building radiative cooling - Shuangjiang Feng; Lei Yao; Mingxin Feng; Haoran Cai; Xu He; Xiaohai Bu; Yuzhong Huang; Yuming Zhou; Man He (Chemical Engineering Journal, 2023)

A case study of a giant reactivated landslide based on NPR anchor cable Newton force early warning - Long-ji Guo; Zhi-gang Tao; Man-chao He; Jian-ning Liu; Massimo Coli (Journal of Mountain Science, 2023)

3D printed stir bar sorptive extraction coupled with high performance liquid chromatography for trace estrogens analysis in environmental water samples - Ning Zhu; Zhekuan Wu; Man He; Beibei Chen; Bin Hu (Analytica Chimica Acta, 2023)

Electroacupuncture Alleviates Neuropathic Pain by Suppressing Ferroptosis in Dorsal Root Ganglion via SAT1/ALOX15 Signaling - Kexing Wan; Min Jia; Hong Zhang; Yuye Lan; Suixi Wang; Kailing Zhang; Zixiao Wang; He Zhu; Xunan Zheng; Yi Luo; Lei Pei; Caihua Wu; et al. (Molecular Neurobiology, 2023)

Stability control measures for roof cutting and NPR supporting of mining roadways in fault areas of kilometre-deep coal mine - Xiao-ming Sun; Jian Wang; Yong Zhang; Wen-chao Zhao; Zhi-biao Guo; Man-chao He; Feng Chen; Cheng-yu Miao (Journal of Mountain Science, 2023)

Comparison of large deformation failure control method in a deep gob-side roadway: A theoretical analysis and field investigation - Jiong Wang; Peng Liu; Man-chao He; Yi-peng Liu; Chang-xin Du (Journal of Mountain Science, 2023)

Spatial-temporal changes of compound temperature-humidity extremes in humid subtropical high-density cities: An observational study in Hong Kong from 1961 to 2020 - Yueyang He; Zixuan Wang; Hau Man Wong; Guangzhao Chen; Chao Ren; Ming Luo; Yuguo Li; Tsz-cheung Lee; Pak Wai Chan; Janice Ying-en Ho; Edward Ng (Urban Climate, 2023)

Sources, size-resolved deposition in the human respiratory tract and health risks of submicron black carbon in urban atmosphere in Pearl River Delta, China - Yuan Liu; Lina Wu; Shan Huang; Qicong Song; Weiwei Hu; Wei Chen; Zhijun Wu; Ruiqi Man; Yao He; Wei Li; Yuwen Peng; Junwen Liu; et al. (Science of The Total Environment, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Effects of extracts of Scutellaria baicalensis and Lonicerae Flos on reproductive performance, milk quality and serum indexes in sows and growth performance in suckling piglets - Zongze He; Chongying Li; Xia Xiao; Hongwei Liu; Man Wang; Xiang Zhou; Jian He (Livestock Science, 2023)

SKN-1/Nrf2-dependent regulation of mitochondrial homeostasis modulates transgenerational toxicity induced by nanoplastics with different surface charges in Caenorhabditis elegans - Man Qu; Long Miao; He Chen; Xing Zhang; Yang Wang (Journal of Hazardous Materials, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Numerical simulation on the impact characteristics between rockfalls of different shapes and gravel cushions - Chun Zhu; Jia-jun Xu; Ya-jun Wang; Man-chao He; Sheng-hua Cui; Xiao-hu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2023)

In-situ elemental quantitative imaging in plant leaves by LA-ICP-MS with matrix-matching external calibration - Zewei Cui; Man He; Beibei Chen; Bin Hu (Analytica Chimica Acta, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Updating emission inventories for vehicular organic gases: Indications from cold-start and temperature effects on advanced technology cars - Zhining Zhang; Junchao Zhao; Hanyang Man; Lijuan Qi; Hang Yin; Zhaofeng Lv; Yuheng Jiang; Junjie Dong; Meng Zeng; Zhitao Cai; Zhenyu Luo; Kebin He; et al. (Science of The Total Environment, 2023)

Failure mechanism and control countermeasures of surrounding rock at deep large section chamber intersection in the Wanfu Coal Mine - Xiao-ming Sun; Zhen-min Qi; Yong Zhang; Cheng-yu Miao; Cheng-wei Zhao; Man-chao He (Journal of Mountain Science, 2023)

Effects of dietary supplementation with saccharicterpenin alleviates diarrhea of piglets - Man Wang; Bing Yu; Jun He; Jie Yu; Yuheng Luo; Junqiu Luo; Xiangbing Mao; Daiwen Chen (Livestock Science, 2023)

Under-loaded operation of an anaerobic-anoxic-aerobic system in dry and wet weather dynamics to prevent overflow pollution: Impacts on process performance and microbial community - Lu-Man Jiang; Zhenjian Zhang; Yunhui Li; Jialei Xu; Kun Wang; Xinya Ding; Junli He; Zhan Qiu; Hua Zhou; Zhen Zhou (Bioresource Technology, 2023)

Evaluation of Cd2+ stress on Synechocystis sp. PCC6803 based on single-cell elemental accumulation and algal toxicological response - Yao Tao; Man He; Beibei Chen; Gang Ruan; Pingping Xu; Yixue Xia; Gaofei Song; Yonghong Bi; Bin Hu (Aquatic Toxicology, 2023)

A renewable platform based on the entropy-driven catalytic amplification and element labeling inductively coupled plasma mass spectrometry for microRNA analysis - Qi Kang; Beibei Chen; Man He; Bin Hu (Analytica Chimica Acta, 2023)

Voltage-gated ion channels in central neurons of Helicoverpa armigera as potential targets for cycloxaprid: a cis-configuration neonicotinoid insecticide - Xiao Liu; Man Chen; Zheng Ma; Yongchuan Yang; Yangxingzi Li; Hongmei Li-Byarlay; Bingjun He (Applied Entomology and Zoology, 2023)

Methods and experiments for collecting information and constructing models of bottom-layer contours in paddy fields - Tuanpeng Tu; Jie He; Xiwen Luo; Lian Hu; Pei Wang; Gaolong Chen; Li Tian; Dawen Feng; Zhimin Wang; Zhongxian Man; Weicong Li; Zhenghui Wei; et al. (Computers and Electronics in Agriculture, 2023)

Development of human dermal PBPK models for the bisphenols BPA, BPS, BPF, and BPAF with parallel-layered skin compartment: Basing on dermal administration studies in humans - Man Hu; Zhichun Zhang; Yining Zhang; Ming Zhan; Weidong Qu; Gengsheng He; Ying Zhou (Science of The Total Environment, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Label-free and selective cholesterol detection based on multilayer functional structure coated fiber fabry-perot interferometer probe - Ruiduo Wang; Minglu Yan; Man Jiang; Yang Li; Xin Kang; Mingxuan Hu; Beibei Liu; Zhengquan He; Depeng Kong (Analytica Chimica Acta, 2023)

circTAB2 inhibits lung cancer proliferation, migration and invasion by sponging miR-3142 to upregulate GLIS2 - Weiling Man; Yumeng Cui; Jie Li; Yanghua Li; Jie Jin; Yang Jin; Xiaojie Wu; Rongbin Zhong; Xiang Li; He Yao; Yanli Lin; Lihe Jiang; et al. (Apoptosis, 2023)

Restored vegetation is more resistant to extreme drought events than natural vegetation in Southwest China - Ying Liu; Zhi Ding; Yanan Chen; Fengqin Yan; Pujia Yu; Weidong Man; Mingyue Liu; He Li; Xuguang Tang (Science of The Total Environment, 2023)

Isolation of atrazine nanobodies enhanced by depletion of anti-carrier protein phages and performance comparison between the nanobody and monoclonal antibody derived from the same immunogen - Qingqing He; Mian Wang; Yajie Zhao; Guiyu Tan; Man Zhang; Rui Feng; Yujie Chen; Baomin Wang; Qing X. Li (Analytica Chimica Acta, 2023)

The Effect of Schizochytrium sp. on Growth, Fatty Acid Profile and Gut Microbiota of Silver Pomfret (Pampus argenteus) - Yuanbo Li; Qijun Le; Man Zhang; Shanliang Xu; Shan He; Xiaojun Yan; Jiabao Hu; Yajun Wang (Journal of Marine Science and Engineering, 2023)
Schizochytrium sp. is a kind of heterotrophic protist, rich in docosahexaenoic acid (DHA). To study the application value of Schizochytrium sp. in fish diet, a 20-day feeding experiment was initiated to evaluate its effect on growth, fatty acid contents, and the gut microbiota of the important economic fish, silver pomfret. In this study, the diets of the treatment group were added with 2% Schizochytrium sp. The fish in the treatment group gained more weight and had a higher growth rate than the control group. The levels of DHA, eicosapentaenoic acid, and polyunsaturated fatty acids in the edible tissue of fish were highly increased in the treatment group after 20 days. After feeding Schizochytrium sp., high-throughput 16S rRNA sequencing showed that the Proteobacteria, Firmicutes and Bacteroidetes were the phyla with the highest abundance, and at the genus and species level, we observed an increased abundance of probiotics. The results indicated that ingestion of Schizochytrium sp. could change the dominant microbiota population, which might lead to accelerated growth and improved unsaturated fatty acid content and fish health. This study provides a reference for Schizochytrium sp. supplementation in fish diets and could aid in the industrialization of silver pomfret.

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Modulated synthesis of S-functionalized magnetic metal organic frameworks-808 for Hg (II) removal - Chi Xu; Man He; Beibei Chen; Bin Hu (Journal of Cleaner Production, 2023)

Asymmetric N-coordinated iron single-atom catalysts supported on graphitic carbon for polysulfide conversion in lithium-sulfur batteries - Songjie He; Juan Yang; Siyu Liu; Xiaoting Wang; Xiaogang Che; Man Wang; Jieshan Qiu (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Oral administration of Synechococcus sp. PCC7942 trans-vp19 and trans-vp (19+28) genes improve the immune and antioxidant capacity in Procambarus clarkii under white spot syndrome virus stress - Jia Yang; Xiao-Ping Chi; Man Li; Wen-hui He; Rui Jia; Pei-Min He (Fish & Shellfish Immunology, 2023)

Ultralight Ti3C2Tx-derivative chrysanthemum-like Na2Ti3O7/Ti3C2Tx MXene quantum dots 3D/0D heterostructure with advanced microwave absorption performance - Man He; Hao Chen; Hao Peng; Yuming Zhou; Zhaoping Song; Yongjuan Wang; Shuangjiang Feng; Xiaohai Bu (Chemical Engineering Journal, 2023)

Skeleton-inspired optical-selective cellulose-based bio-film as passive radiative cooler and the energy-saving performance evaluation - Shuangjiang Feng; Yuming Zhou; Chenghuan Liu; Tao Zhang; Xiaohai Bu; Yuzhong Huang; Man He (Chemical Engineering Journal, 2023)

Underwater self-sustaining combustion and micro-propulsion properties of Al@FAS-17/PTFE-based direct-writing nanothermite - Haifeng Yang; Chuanhao Xu; Weimiao Wang; Pengfei Tang; Xiaodong Li; Shanshan He; Hebin Bao; Shuaishuai Man; Deyun Tang; Xueming Li; Guangcheng Yang; Zhiqiang Qiao (Chemical Engineering Journal, 2023)

Nitrogen-doped porous carbon electrode for aqueous iodide redox supercapacitor - Man Wang; Juan Yang; Siyu Liu; Xiaogang Che; Songjie He; Guohua Chen; Jieshan Qiu (Chemical Engineering Journal, 2023)

5′-Nucleotidase is dispensable for the growth of Salmonella Typhimurium but inhibits the bactericidal activity of macrophage extracellular traps - Man Qian; Ke Xu; Mengke Zhang; Junhui Niu; Tianxiang Zhao; Xiaoli Wang; Yanyan Jia; Jing Li; Zuhua Yu; Lei He; Yinju Li; Tingcai Wu; et al. (Archives of Microbiology, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Alleviating the Influence of Circadian Rhythms and Drug Properties to the Release of Paliperidone Gel Matrix Tablets with Compression Coating Technology and Microenvironment Shaping - Zherui Zhang; Shumin Chen; Man Wen; Haibing He; Yu Zhang; Tian Yin; Jingxin Gou; Xing Tang (AAPS PharmSciTech, 2022)

Comparative Study of Nine Intact Rock Failure Criteria via Analytical Geometry - Peng-fei He; Xiao-dong Ma; Man-chao He; Zhi-gang Tao; Dong-qiao Liu (Rock Mechanics and Rock Engineering, 2022)

Transcriptomics and transmission ultrastructural examination reveals the nephrotoxicity of cadmium in laying hens - Man Zhao; Wenbo He; Can Tao; Beiyu Zhang; Shuai Wang; Zhangjian Sun; Zhifeng Xiong; Niya Zhang (Environmental Science and Pollution Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Eco-geological environment quality assessment based on multi-source data of the mining city in red soil hilly region, China - Fei-fei Zhao; Man-chao He; Yun-tao Wang; Zhi-gang Tao; Chun Li (Journal of Mountain Science, 2022)

Hepatoprotective effect of total flavonoids from Glycyrrhiza uralensis Fisch in liver injury mice - San-hu Gou; Miao He; Bei-bei Li; Ning-yi Zhu; Jing-man Ni (Natural Product Research, 2021)

Neonatal Anesthesia by Ketamine in Neonatal Rats Inhibits the Proliferation and Differentiation of Hippocampal Neural Stem Cells and Decreases Neurocognitive Function in Adulthood via Inhibition of the Notch1 Signaling Pathway - He Huang; Chao Zhao; Qian Hu; Qiang Liu; Yi-Man Sun; Chen Chen; Hui Huang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2021)

Numerical investigation on the fatigue failure characteristics of water-bearing sandstone under cyclic loading - Chun Zhu; Man-chao He; Bei Jiang; Xin-zhan Qin; Qian Yin; Yu Zhou (Journal of Mountain Science, 2021)

Dynamic process of rock avalanche and dynamic interaction between rock avalanche and hazard-bearing bodies - Zhong Fu Wang; Man He; Yan Wang; Jingzhuo Yang; Haoyuan Li (Arabian Journal of Geosciences, 2021)

Variational Quality Control of Non-Gaussian Innovations in the GRAPES m3DVAR System: Mass Field Evaluation of Assimilation Experiments - Jie He; Xulin Ma; Xuyang Ge; Juanjuan Liu; Wei Cheng; Man-Yau Chan; Ziniu Xiao (Advances in Atmospheric Sciences, 2021)

LINC00152 mediates CD8+ T-cell infiltration in gastric cancer through binding to EZH2 and regulating the CXCL9, 10/CXCR3 axis - Jinqing Ou; Pingguang Lei; Zhenling Yang; Man Yang; Lingmin Luo; Hongdan Mo; Guijin Luo; Junhui He (Journal of Molecular Histology, 2021)

Efficiency comparison of B6(Cg)-Tyrc−2j /J and C57BL/6NTac embryos as hosts for the generation of knockout mice - Yu’e Ma; Lei He; Lijie Xiang; Jie Zhang; Jing Wang; Wenjing Zhu; Wenni Cao; Yichen Zhu; Man Gao; Fei Zhou; Zhiwei Liu (Transgenic Research, 2021)
Careful selection of the host embryo is critical to the efficient production of knockout (KO) mice when injecting mouse embryonic stem (mES) cells into blastocysts. B6(Cg)-Tyr c−2j /J (B6 albino) and C57BL/6NTac (B6NTac) strains of mice are widely used to produce host blastocysts for such procedures. Here, we tested these two strains to identify an appropriate match for modified agouti C57BL/6N (JM8A3.N1) mES cells. When comparing blastocyst yield, super-ovulated B6NTac mice produced more injectable blastocysts per female than B6 albino mice (8.2 vs. 5.4). There was no significant difference in birth rate when injected embryos were transferred to the same pseudopregnant recipient strain. However, the live birth rate was significantly higher for B6NTac blastocysts than B6 albino blastocysts (62.7% vs. 50.2%). In addition, the proportion of pups exhibiting high-level and complete chimerism, as identified by coat color, was also significantly higher in the B6NTac strain. There was no obvious difference in the efficiency of germline transmission (GLT) when compared between B6NTac and B6 albino host embryos (61.5% vs. 63.3% for mES clones; 64.5% vs. 67.9% for genes, respectively), thus suggesting that an equivalent GLT rate could be obtained with only a few blastocyst injections for B6NTac embryos. In conclusion, our data indicate that B6NTac blastocysts are a better choice for the microinjection of JM8A3.N1 mES cells than B6 albino blastocysts.

Identification and verification of key functional groups of biochar influencing soil N2O emission - Dan Yuan; Haijing Yuan; Xiaodong He; Huixian Hu; Shuping Qin; Tim Clough; Nicole Wrage-Mönnig; Jiafa Luo; Xinhua He; Man Chen; Shungui Zhou (Biology and Fertility of Soils, 2021)

The collision experiment between rolling stones of different shapes and protective cushion in open-pit mines - Chun Zhu; Man-chao He; Murat Karakus; Xiao-hu Zhang; Zhen Guo (Journal of Mountain Science, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Model test on support scheme for carbonaceous slate tunnel in high geostress zone at high depth - Zhi-gang Tao; Shu-lin Ren; Gan Li; Hao-tian Xu; Sen-lin Luo; Man-chao He (Journal of Mountain Science, 2021)

Stability analysis of open-pit gold mine slopes and optimization of mining scheme in Inner Mongolia, China - Shu-lin Ren; Zhi-gang Tao; Man-chao He; Shi-hui Pang; Meng-nan Li; Hao-tian Xu (Journal of Mountain Science, 2020)

Inversion of time-domain airborne EM data with IP effect based on Pearson correlation constraints - Man Kai-Feng; Yin Chang-Chun; Liu Yun-He; Ren Xiu-Yan; Sun Si-Yuan; Miao Jia-Jia; Xiong Bin (Applied Geophysics, 2020)

How aging process changes characteristics of vehicle emissions? A review - Huan Liu; Lijuan Qi; Chunsheng Liang; Fanyuan Deng; Hanyang Man; Kebin He (Critical Reviews in Environmental Science and Technology, 2020)

Mortality risk of a future heat event across a subtropical city: implications for community planning and health policy - Hung Chak Ho; Ka Ming Wai; Minhao He; Ta-Chien Chan; Chengbin Deng; Man Sing Wong (Natural Hazards, 2020)

Multi-lineage differentiation and clinical application of stem cells from exfoliated deciduous teeth - Fei Xie; Jie He; Yingyi Chen; Ziqi Hu; Man Qin; Tianqian Hui (Human Cell, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Genome-Wide Identification and Expression Analysis of the NAC Transcription Factor Family in Pineapple - Qing He; Yanhui Liu; Man Zhang; Mengyan Bai; S. V. G. N. Priyadarshani; Mengnan Chai; Fangqian Chen; Youmei Huang; Liping Liu; Hanyang Cai; Yuan Qin (Tropical Plant Biology, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Genome-Wide Classification and Evolutionary and Functional Analyses of the VQ Family - Hanyang Cai; Man Zhang; Yanhui Liu; Qing He; Mengnan Chai; Liping Liu; Fangqian Chen; Youmei Huang; Maokai Yan; Heming Zhao; Jerming Hu; Yuan Qin (Tropical Plant Biology, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Cellular stress and redox activity proteins are involved in gastric carcinogenesis associated with Helicobacter pylori infection expressing high levels of thioredoxin-1 - Yan-yan Shi; Jing Zhang; Ting Zhang; Man Zhou; Ye Wang; He-jun Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2018)

Nitrogen leaching losses following biogas slurry irrigation to purple soil of the Three Gorges Reservoir Area - Jianbo Cheng; Yucheng Chen; Tengbing He; Renlu Liu; Man Yi; Zhimin Yang (Environmental Science and Pollution Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Identifying and assessing human activity impacts on groundwater quality through hydrogeochemical anomalies and NO3 −, NH4 +, and COD contamination: a case study of the Liujiang River Basin, Hebei Province, P.R. China - Cong Peng; Jiang-Tao He; Man-li Wang; Zhen-guo Zhang; Lei Wang (Environmental Science and Pollution Research, 2018)

Links between Western Pacific Subtropical High and vegetation growth in China - Mei Huang; Man Hao; Shaoqiang Wang; Li Dan; Fengxue Gu; Zhaosheng Wang; He Gong (Journal of Geographical Sciences, 2018)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Characteristics of low altitude ionospheric electric field over Hainan Island, China - RenKang Li; Tao Chen; Feng Man; XiuJie Jiang; Jing Luo; ZhaoHai He; HuiMing Zhang; LinFeng Wang; Cheng Liu; Francisco Carlos de Meneses; GuoJun Wang; JiYao Xu (Science China Earth Sciences, 2017)

Quantification and bio-assay of α -glucosidase inhibitors from the roots of Glycyrrhiza uralensis Fisch. - San-hu Gou; Jie Liu; Miao He; Yin Qiang; Jing-man Ni (Natural Product Research, 2016)

Involvement of polyphosphate kinase in virulence and stress tolerance of uropathogenic Proteus mirabilis - Liang Peng; Qiao Jiang; Jia-Yun Pan; Cong Deng; Jing-Yi Yu; Xiao-Man Wu; Sheng-He Huang; Xiao-Yan Deng (Medical Microbiology and Immunology, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

Regional land-use allocation with a spatially explicit genetic algorithm - Yaolin Liu; Man Yuan; Jianhua He; Yanfang Liu (Landscape and Ecological Engineering, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Common polymorphisms (rs2241766 and rs1501299) in the ADIPOQ gene are not associated with hypertension susceptibility among the Chinese - Bo Xi; Dan He; Qijuan Wang; Jian Xue; Man Liu; Jun Li (Molecular Biology Reports, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Meta-analysis of association between cytokine gene polymorphisms and lung cancer risk - Wen-jia Peng; Qian He; Jin-xia Yang; Bing-xiang Wang; Man-man Lu; Song Wang; Jing Wang (Molecular Biology Reports, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

Synergistic promotion of gibberellin and cytokinin on direct regeneration of floral buds from in vitro cultures of sepal segments in sinningia speciosa hiern - Ji-Liang Pang; Li-Lin Wang; Jiang-Qin Hu; Tai-He Xiang; Hai-Man Liang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Ecological restoration:Our hope for the future? - Xu-gao Wang; Xiu-zhen Li; Hong S He; Yuan-man Hu (Chinese Geographical Science, 2004)

Effect of the antidepressant maprotiline on calcium movement and the viability of renal tubular cells - Shu-Shong Hsu; Wei-Chung Chen; Bang-Ping Jiann; Jin-Shyr Chen; Jong-Khing Huang; Hong-Tai Chang; He-Hsiung Cheng; Yuk-Keung Lo; Chin-Man Ho; Chung-Ren Jan (Archives of Toxicology, 2004)

Sedimentary cycles of trace elements in Salawusu River Valley since 150 ka BP - Yao Chun-xial; Li Bao-sheng; Jin He-ling; David Dian Zhang; Yan Man-cun; Zhu Yi-zhi; Li Hou-xin; Zhang Yu-hong; Luo Kai-li (Journal of Geographical Sciences, 2002)

CaCO3 cycles in salawusu river basin since 150ka B.P. - Kai-li Luo; Bao-sheng Li; Yi-zhi Zhu; He-ling Jin; David Dian Zhang; Man-cun Yan; Hou-xin Li; Chun-xia Yao; Yu-hong Zhang (Chinese Geographical Science, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)